Dampak Pemanfaatan Smartphone terhadap Norma Sopan Santun pada Remaja di Kelurahan Teluk Lerong Ulu Kecamatan Sungai Kunjang Kota Samarinda - Kholifaturrosidah Kholifaturrosidah; Moh. Bahzar; M. Jamil (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study was to determine the impact of smartphone use on politeness norms among adolescents in Teluk Lerong Ulu Village and the polite behavior of adolescents who use smartphones in Teluk Lerong Ulu Village. The study was conducted in Teluk Lerong Ulu Village, precisely on Banggeris Street, with the subjects of the study being several adolescents and also the community through the stages of observation, interviews, and documentation using qualitative descriptive research. The results of the study indicate that the use of smartphones has a positive impact as an effective means of obtaining information about politeness, facilitating communication, and increasing ethical awareness on social media. However, excessive use of smartphones also has a negative impact on adolescents, such as decreasing the ability of adolescents to interact directly, ignoring the presence of people around them, and increasing the use of coarse and impolite language in digital communication. The polite behavior of adolescents who use smartphones in Teluk Lerong Ulu Village includes politeness in attitude, behavior and speech.These three aspects complement each other so as to create harmonious sosial interactions, build adolescent personalities so that they are able to position themselves appropriately in everyday life.